Pedicle Screw-Rod Fixation for Treatment of Lumbosacral Intervertebral Disc Degeneration in Dogs with Low Back Pain. (May 2014) - Meij, B.; Tellegen, A.; Willems, N.; Tryfonidou, M.
Introduction: Low back pain in nonchondrodystrophic large breed dogs is a common problem and the most common cause is degenerative lumbosacral stenosis (DLSS). DLSS is characterized by intervertebral disc (IVD) degeneration of L7-S1, disc bulging, disc herniation, spinal canal stenosis, compression of neuronal tissue (cauda equina), thickened nerve roots (neuritis), soft tissue and bony proliferations, and foraminal stenosis. This ultimately results in discogenic and neurogenic pain. DLSS in dogs maybe treated conservatively or surgically. The most common surgical treatment is decompressive dorsal laminectomy and partial discectomy but in severe degenerated IVDs or in cases with foraminal stenosis and neuritis this may not be sufficient to treat low back pain. In these cases, pedicle screw-rod fixation (PSRF) can be performed. The aim of PSRF was to increase the intervertebral foraminal space for the exiting nerves and to promote spinal fusion. Distraction of the peripheral joints is one of the most promising new techniques in allowing chondrocytes to initiate repair of damaged cartilage in osteoarthritis. IVD degeneration, such as osteoarthritis, is also characterized by a decreasing number of nucleus pulposus cells and disc matrix. PSRF allows distraction of the IVD and may initiate, in a similar fashion as in joints, repair of the disc matrix. This was investigated in a pilot study in a dog that underwent temporary distraction and follow-up with magnetic resonance imaging (MRI). The aim of the present study was to investigate the effectiveness of PSRF in dogs with severe lumbosacral disc degeneration, to assess the effect of PSRF on the intervertebral foramina and on spinal fusion and, in a pilot study, to investigate the regenerative role of temporary distraction on the degenerated lumbosacral disc. Materials and Methods: Eleven dogs with confirmed diagnosis of DLSS and IVD degeneration underwent PSRF of the lumbosacral junction (Fig. 1 ). In 10 (out of the 11) dogs, PSRF was combined with dorsal laminectomy, disc fenestration, and various techniques to promote spinal fusion. In a subset of these patients (4 of 10 dogs), permanent distraction of the lumbosacral joint before PSRF was applied. In order to investigate the effect of temporary distraction of the degenerated lumbosacral joint, the PSRF was applied on the distracted joint for 3 months and removed thereafter. During follow-up, the dogs were monitored using questionnaires to owners and by clinical evaluation, diagnostic imaging with computed tomography and MRI, and measurement of ground reaction forces by force plate analysis. In the 4 dogs in which permanent distraction was applied, the increase in the intervertebral foramen was measured and in 1 dog the effect of temporary distraction on the disc matrix was evaluated on MRI. Results: Clinical evaluation, responses of questionnaires to owners, and force plate data showed improvement or complete resolution of clinical signs after pedicle screw-rod fixation in 11 dogs during follow-up periods ranging from 5 months to 4 years. Diagnostic imaging showed no implant failures. In none of the 10 dogs was intervertebral body bone fusion of the lumbosacral joint achieved. In the dogs in which permanent distraction was applied, postoperative imaging showed significant enlargement of the intervertebral foramen between L7 and S1 (Fig. 1 ). In the dog with temporary distraction, MRI indicated no changes in the IVD signal 3 months after removal of the PSRF device. Fig. 1 Canine lumbosacral spine segment in a dog with degenerative lumbosacral stenosis before and after distraction plus pedicle screw-rod fixation (PSRF). Conclusion: Pedicle screw-rod fixation offers a surgical treatment option for large dogs with severe degenerative lumbosacral stenosis. However, PSRF alone does not result in intervertebral body fusion between L7 and S1 and for that additional methods are necessary. Distraction and PSRF is effective in enlarging the intervertebral foramina and alleviating clinical signs. Temporary distraction alone, to initiate regeneration of the intervertebral disc matrix, did not have adverse effects and is an interesting concept for further investigation. Disclosure of Interest None declared